Utilization of Cable Screen Earthing Current for Detection and Location of Earth Faults in Medium Voltage Networks - Krzysztof Łowczowski; Józef Lorenc; Magdalena Czerniak; Józef Zawodniak (Energy Engineering and Control Systems, 2021)
The paper presents issues related with detection and location of earth faults in medium voltage (MV) networks. Attention is paid on cable and cable-overhead lines. The criterion value – cable screen earthing current is presented. Afterwards, the method of utilization of the cable screen earthing current for detection and location of earth faults is described. The next part of the paper presents the results of simulation research for different variants of earth faults in cable and cable-overhead lines. The presented relations are the basis of the developed algorithm of detection and localization of earth faults. The presented considerations were confirmed by an experiment performed in the MV network.